Integration processes in the enterprises management of tourism industry - Шамара, Ірина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
This article considers the main theoretical approaches to the formation of the integration processes in the enterprises management of tourism industry. The article reveals priorities  of the objectives for the formation and implementation of modern organizational and management practices in the management of enterprises in the tourism industry in connection with the entry of Ukraine to a highly economic, cultural and legal field in Europe and the world. The article analyzes economic benefits of the consolidation activities and the integration structures formation, such as: harmonization of the economic integration and interests of the participants to improve their performance. The essence, the cause of the existing models of integration in the tourism industry – both vertical and horizontal were revealed.The vertical integration of the «forward» and «backward» was considered. The forms of integration, such as the concentration and co–operation were considered too. The integration processes in the management of the enterprises, which covered the tourist market of Ukraine were analyzed. The author pays attention to the form of the franchise business in Ukraine. The article considres that the competitive advantage from the development and implementation of the integration strategy in the management of enterprises of the tourism industry, such as:  the usage of the single marketing; the assistance in training and staff development; the usage of well–known brand, image; the systematic usage of the flexible pricing policy; the operation of the single reservation system services; the ensuring of the high quality service.